Numerical analysis of vanadium crossover effects in all-vanadium redox flow batteries. (20th September 2015) - Won, Seongyeon; Oh, Kyeongmin; Ju, Hyunchul
Highlights: The effects of vanadium crossover of VRFBs are examined by numerical method. The evolution of vanadium ions are investigated with fresh and degraded membranes. The magnitude of crossover is studied with various thickness of membrane. The capacity loss is intensified as the membrane is degraded. ABSTRACT: In this work, a crossover model is newly developed to account rigorously for the crossover of vanadium ions through the membrane and resultant side reactions occurring in both positive and negative electrodes. The crossover model is then numerically coupled with previously developed three-dimensional (3-D), transient, thermal VRFB model in which key physicochemical phenomena including the electrochemical reactions, waste heat generation, resultant species and heat transport are all included. Using the comprehensive VRFB model, we investigate the effects of vanadium crossover between the negative and positive electrodes during a single charge/discharge cycle. Numerical simulations successfully capture capacity loss related to vanadium crossover, clearly showing the difference in species distributions due to side reactions. The results show that due to effect of vanadium ion crossover, more charging time and less discharging time have been achieved.